1749-51 Mass. Acts 339, An Act for Preventing and Suppressing of Riots, Routs and Unlawful Assemblies, ch. 12. - (:unkn) unknown (General Publisher, 1751)
if any Persons to the Number of Twelve or more, being Arm’d with Clubs or other Weapons, or if any Number of Persons consisting of Fifty or upwards, whether armed or not, shall be unlawfully riotously or tumultuously assembled; any Justice of the Peace, Field-Officer or Captain of the Militia, Sheriff of the County or Under-Sheriff, or any Constable of the Town, shall among the Rioters, or as near to them as he can safely come, command Silence while Proclamation is making, and shall openly make Proclamation in these or the like Words,
--
Keywords: GOING ARMED